2010
DOI: 10.1016/j.foodqual.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumer product profiling techniques and their linkage to a quantitative descriptive analysis

Abstract: a b s t r a c tConsumer's voice is crucial for new product development. One way to capture it is to ask consumers to describe products and to quantify their perception of this description. In this context four profiling methods; sorting, projective mapping, flash profile and repertory grid method (RGM) were explored among target consumers of hot beverages in two European countries (UK and France) with the assumption that meaningful sensory descriptors can be generated and quantified, and that product maps can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
1
22

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 23 publications
8
131
1
22
Order By: Relevance
“…This is also generally consistent with previous studies comparing holistic methodologies and attribute-based methodologies in different products categories. For example, in a study on hot beverages Moussaoui and Varela (2010) found that FP and RGM gained benefit of providing a quantitative product mapping compared to Sorting and Projective…”
Section: Comparison Of Napping and Flash Profilementioning
confidence: 99%
See 2 more Smart Citations
“…This is also generally consistent with previous studies comparing holistic methodologies and attribute-based methodologies in different products categories. For example, in a study on hot beverages Moussaoui and Varela (2010) found that FP and RGM gained benefit of providing a quantitative product mapping compared to Sorting and Projective…”
Section: Comparison Of Napping and Flash Profilementioning
confidence: 99%
“…Assessors are asked to list the sensory characteristics that best describe the differences among the samples and then rank all the samples for each of their individual attribute lists (Dairou & Sieffermann, 2002). FP has already been used for sensory evaluation in many different food product categories, including jams (Dairou & Sieffermann, 2002), dairy products (Delarue & Sieffermann, 2004), hot beverages (Moussaoui & Varela, 2010), lemon iced teas (Veinand et al, 2011), fish nuggets (Albert et al, 2011), and liver pâté (Dehlholm, Brockhoff, Meinert, Aaslyng, & Bredie, 2012). One of the drawbacks of this method is that, since assessors are not imposed on the use of a common vocabulary, the semantic interpretation of FP results can be complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A equipe é frequentemente monitorada com relação ao seu desempenho (concordância, capacidade discriminativa, repetibilidade) e à reprodutibilidade, individual ou do grupo como um todo, durante os treinamentos, com o objetivo de alcançar resultados mais precisos e, portanto, mais confiáveis e consistentes (NBR ISO 11132 ABNT, 2016;MOUSSAOUI;VARELA, 2010).…”
Section: Análise Descritiva Quantitativaunclassified
“…The change in the stress in relation with the number of dimensions of the configuration was similar for both replicates, indicating a good repeatability in both experiments (Table 3). The good performance of sorting may be related to the set of samples used, since maize has many sensory attributes that interact, leading consumers naturally to use many sensory attributes for the formation of groups and description of samples (Moussaoui & Varela, 2010). According to the configuration structure observed and the distance measured between samples in the first experiment, four groups of varieties can be formed (Figure 1a).…”
Section: Similarity Of Maize Varietiesmentioning
confidence: 99%